Durability of Engineered Cementitious Composite (ECC) Incorporating Crumb Rubber and Nano Silica with respect to Chemical Attack Resistance - Mahendran, Inthiran (IRC, 2019)
The growing amount of the waste tires have raised ever-increasing environmental concern with the development of the automobile industries. Therefore, utilization of crumb rubber in Engineered Cementitious Composite (ECC) has attracted attention in the construction industry. During the elevated temperature, the crumb rubber (CR) melts and creates escape routes for build-up pressure due to moisture and the matrix. The main objective of this study is to determine durability of Engineered Cementitious Composite (ECC) incorporating crumb rubber and nano silica with respect to chemical attack resistance. Response Surface Methodology (RSM) is used to obtain 13 mix design with the percentage of crumb rubber ranging from 0% to 6.035%. The percentage of nano silica in the mixture are ranging from 0% to 4.83%. PVA fibers are kept at a constant percentage of 2% to avoid balling effect.